PEMANFAATAN MORINGA OLEIFERA PADA IBU HAMIL BERKAITAN DENGAN BUDAYA DI PUSKESMAS KALIBAGOR KABUPATEN BANYUMAS - Dewi Ambarwati (Jurnal Informasi Kesehatan Indonesia (JIKI), 2021)
Background:Lack of iron affects the formation of hemoglobin (Hb) levels, resulting in inadequate transport of oxygen to all body tissues. Iron deficiency anemia in pregnant women can affect the growth and development of the fetus they contain. Moringa plant(Moringa oleifera)is a tropical plant that contains nutrients that can help increase heme and hemoglobin levels in the blood in pregnant women. The purpose of this study was to describe the use of Moringa Aloefera in pregnant women at Puskesmas Kalibagor, Banyumas Regency. Subjects and Methods:This research was conducted in the working area of ??Puskesmas Kalibagor, Banyumas Regency, using a qualitative method with a case study (case study). Data collection using in-depth interviews (indept interview) to pregnant women, traditional birth attendants, and midwives as triangulation. Analysis of this research data using thematic content analysis. Results:Knowledge of pregnant women about the use of Moringa leaves is very important to see the high nutritional content of Moringa leaves, so that it can improve the health status of pregnant women, especially those caused by iron deficiency anemia. Pregnant women at the Kalibagor Health Center have less knowledge about the benefits of Moringa leaves. All pregnant women said that they did not use Moringa leaves to ward off evil spirits/unseen creatures or traditional rituals. Lack of knowledge in the use of Moringa leaves is one of the causes of pregnant women not using Moringa leaves. Culture and community heritage related to food processing that has not been diverse related to the use of Moringa leaves is also a factor in the lack of use of Moringa leaves. Conclusion:Knowledge, culture, information from both health workers and traditional speech from parents/ancestors are factors that can affect the use of Moringa leaves. Keywords:Anemia, Pregnancy, Culture, Moringa